Flight patterns of Hedya dimidioalba, Spilonota ocellana and Pandemis heparana (Lep.: Tortricidae) based on data from pheromone traps - Jitka Stará; František Kocourek (Plant Protection Science, 2001)
During 1992-1999 the flight activity of Hedya dimidioalba, Spilonota ocellana and Pandemis heparana was investigated by pheromone traps placed in six apple orchards and a plum orchard in Central and East Bohemia. The cumulative catches of each species were plotted against time of the catch expressed as the sum of degree-days above 10°C (H. dimidioalba and S. ocellana) and 8°C (P. heparana) and approximated by Richards' function. Common parameters of Richards' function could be found for Hedya dimidioalba and Spilonota ocellana from all localities. In Pandemis heparana the flight pattern was different for groups of localities with similar climatic conditions. It was found that the beginning, peak and end of the flight activity of these species in the Czech Republic can be reasonably predicted.